1997
DOI: 10.1093/nar/25.16.3275
|View full text |Cite
|
Sign up to set email alerts
|

The Cryphonectria parasitica plasmid pUG1 contains a large ORF with motifs characteristic of family B DNA polymerases

Abstract: The isolation and characterization of the circular mitochondrial plasmid pUG1 from the ascomycete Cryphonectria parasitica is described. The entire sequence (4182 bp) was obtained and high similarities to DNA-dependent DNA polymerases were revealed. Strikingly common features with the DNA polymerases encoded by the Neurospora intermedia plasmids Fiji and LaBelle, such as matches to the conserved motifs A and B and the presence of TTD instead of DTD in motif C, were found, suggesting the existence of a distinct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Consistent with this assertion, four of the bacterial and five mitochondrial piPolBs were encoded by circular plasmids ( Figure S1 ). Notably, the mitochondrial plasmids carry no other genes than those encoding piPolB ( Gobbi et al., 1997 , Li and Nargang, 1993 , Schulte and Lambowitz, 1991 ), suggesting that, following the introduction of a mitochondrial ancestor into a proto-eukaryotic host, the MGE underwent reductive evolution.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Consistent with this assertion, four of the bacterial and five mitochondrial piPolBs were encoded by circular plasmids ( Figure S1 ). Notably, the mitochondrial plasmids carry no other genes than those encoding piPolB ( Gobbi et al., 1997 , Li and Nargang, 1993 , Schulte and Lambowitz, 1991 ), suggesting that, following the introduction of a mitochondrial ancestor into a proto-eukaryotic host, the MGE underwent reductive evolution.…”
Section: Resultsmentioning
confidence: 99%
“…The TLS capacity might be of particular importance for mitochondrial pipolins, which, similar to mitochondrial genomes, are likely to be frequently exposed to reactive oxygen species regularly produced during normal mitochondrial respiration ( Valentine et al., 1998 ). Previous studies have shown that replication of pCRY1-like pipolins from fungal mitochondria ( Gobbi et al., 1997 , Li and Nargang, 1993 ) can be initiated from multiple origins rather than from a fixed origin ( Baidyaroy et al., 2012 ). However, this observation remained unexplained.…”
Section: Discussionmentioning
confidence: 99%
“…kalilo and maranhar associated with senescence, the Ascobolus immersus PAI2 [9] and the Podospora anserina pAL2-1 involved in an increased life span [10]. In the phytopathogenic fungus Cryphonectria parasitica, the circular mitochondrial plasmid pUG1 occurs in virulent strains exhibiting a senescent phenotype [11]. An almost homogeneous family of mitochondrial plasmids related to pUG1 has spread among the North American and European C. parasitica populations [12].…”
Section: Introductionmentioning
confidence: 99%